ON THE CONCEPT OF PUNISHMENT AND ITS CONTENT (Scientific journal of the Fergana State University, 2024)
In this article, the concept of punishment, its essence, its types, punishment is not the main purpose of punishment, but education of the person who committed the offense in the spirit of respect for the Constitution and laws, ensuring law and order, illegal acts by this person and other persons. some opinions about the prevention of its occurrence have been stated.